Na+/K+-ATPase: a multifunctional target in type 2 diabetes and pancreatic islets - Mou, Lisha; Fu, Zhenkun; Wang, Tony Bowei; Chen, Yuxian; Luo, Ziqi; Wang, Xinyu; Pu, Zuhui (Frontiers in Immunology, 2025)
Type 2 diabetes (T2D) is a widespread metabolic disorder marked by hyperglycemia, arising from insulin resistance and relative insulin deficiency. This review investigates the critical role of Na+/K+-ATPase (NKA), a transmembrane protein essential for maintaining cellular ion gradients, in the pathophysiology of T2D. We provide an overview of NKA’s biological functions, emphasizing its involvement in cellular signaling pathways, insulin secretion, and glucose homeostasis. The potential of NKA as a therapeutic target for T2D is analyzed, showcasing innovative strategies such as NKA activators, gene therapy, and stem cell therapy aimed at enhancing NKA activity to achieve better glycemic control. Additionally, NKA’s multifunctional role in maintaining cell viability and modulating immune responses in islet transplantation may offer potential benefits for improving transplant outcomes. By elucidating the complex interactions between NKA and T2D, this review aims to shed light on developing novel therapeutic interventions that meet the multifaceted needs of individuals suffering from this chronic condition, ultimately improving their health outcomes.